Olanzapine-induced neutropenia - Kirti Malhotra; Priscilla Vu; Danielle H. Wang; Hank Lai; Lawrence R. Faziola (Mental Illness)
Olanzapine-induced neutropenia is a rare adverse effect that is currently poorly described in literature. Although neutropenia is a known adverse effect of clozapine, it has been associated with the use of other antipsychotic medications like olanzapine. This case report describes and reviews a case of olanzapine-induced neutropenia in a schizophrenic patient. Although the mechanism of antipsychotic-induced neutropenia is still debated, this report attempts to discuss current theories as well as supply evidence in literature of this rare but potentially dangerous adverse effect.